Two-dimensional (PEA)2PbBr4 perovskite single crystals for a high performance UV-detector. Issue 6 (18th January 2019) - Zhang, Yunxia; Liu, Yucheng; Xu, Zhuo; Ye, Haochen; Li, Qingxian; Hu, Mingxin; Yang, Zhou; Liu, Shengzhong (Frank)
Abstract : A centimeter-sized high-quality two-dimensional (PEA)2 PbBr4 single crystal was prepared, which exhibited superior UV photo-response performance. Abstract : Two-dimensional (2D) metal halide perovskites have shown great potential in high performance optoelectronic applications due to their intrinsic quantum well structure, enhanced moisture- and photo-stability. Unfortunately, there is still no effective method to produce large-size 2D hybrid perovskite single crystals, and consequently there is lack of research on its optoelectronic applications. Herein, we report the utilization of a controlled evaporation process to grow well-defined large-size (>200 mm 2 ) 2D (PEA)2 PbBr4 (C6 H5 CH2 CH2 NH3 +, PEA + ) single crystals. Upon careful examination of the crystal growth kinetics, it was found that the optimum temperature for the growth of (PEA)2 PbBr4 single crystal wafer was 23 ± 0.5 °C. The wafers that were harvested showed high mu-tau ( μτ ) product, superior environmental stability and irradiation resistance. Furthermore, an array of planar-type UV photodetectors were designed and fabricated with extremely low dark current (∼10 −13 A), large ON/OFF current ratio (∼10 5 ), very high specific detectivity (∼10 13 cm Hz 1/2 W −1 ) and fast response rate (∼0.4 ms). All the above performance data are among the best achieved compared to those of the state-of-the-art materials including ZnO, TiO2 and GaN in the field. It makes us believe that the availability of these materials may pave the way for ultrafast optical computing and optical communications.